Obrazovanje nastavnika stranih jezika u Hrvatskoj = Education of foreign language teachers in Croatia - Mihaljević-Djigunović, Jelena (2008)
The author compares EFL teacher education curricula from two Croatian universities. Her focus is on teacher competences as outcomes of teacher education.
ENG